A 22-Year Cross-Sectional Cohort Study of the Emotional and Behavioral Characteristics of Students With Emotional Disturbance. (May 2023) - Epstein, Michael H.; Cullinan, Douglas; Lambert, Matthew C.; Kauffman, James M.; Katsiyannis, Antonis; Mason, W. Alex
The present study was conducted to determine whether the problem characteristics of U.S. students school-identified with emotional disturbance (ED) have changed over two decades. We used data from a teacher rating instrument designed to measure the five problem characteristics of ED, as stated in its Individuals with Disabilities Education Act (IDEA) definition. These data were collected in the process of norming the instrument for 1998 and again for 2020. Comparison of the 1998 and 2020 students school-identified with ED showed that the 1998 group had significantly more problematic functioning on two characteristics, namely, Relationship Problems and Inappropriate Behavior, but no more problematic differences on Inability to Learn, Unhappiness or Depression, and Physical Symptoms or Fears. In addition, analyses of selected items gave more context to the main results. Study limitations, future research, and implications are discussed.